Analisis Pengaruh Corporate Governance, Corporate Risk, Earnings Management, Leverage Dan Liquidity Terhadap Tindakan Pajak Agresif (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Periode 2012-2015) - Putri, Handayani Widiyanto; , Drs. Muhammad Abdul Aris, M.Si (2017)
The objective of this study is to analyze the influence of corporate governance, corporate risk, earnings management, leverage, and liquidity to tax aggresiveness in companies listed in Indonesia Stock Exchange during the period of 2012-2015. Sample was determined by purposive sampling method. From this method, there was collected 32 bservations from 8 companies based on multiple linier regression analysis. The result showed that corporate governance and corporate risk had negative significantly effect to tax aggresiveness. Earnings management and liquidity had positive significantly effect to tax aggresiveness. Whereas leverage had no significantly effect to tax aggresiveness. This result were consistent to previous studies from Hidayanti and Laksito (2013), Budiman and Setiyono (2012), I Nyoman, et al. (2015), Kurniasih and Sari (2013), Prakosa (2014),and Darmawan and Sukartha (2014).